What is and is not Hellenistic Judaism? - Rios, Cesar Motta (2017)
Abstract: in the studies of Judaism in antiquity, and in the field of general History as well, it is usual to find references to Hellenistic Judaism, usually in opposition to Palestinian Judaism. In this article, I reflect on the concept of Hellenistic Judaism through the reference to specific texts and authors identified as part of this branch of Ancient Judaism. I demonstrate the frequent simplification that this expression imposes to an extremely complex intercultural phenomenon. I do not suggest its complete abandon, but a minded use of it, which includes the recognition of the impressive existent diversity.O Que É e Não é Judaísmo Helenístico?Resumo: em estudos sobre o judaísmo na Antiguidade, bem como da História geral, é comum encontrar referências ao judaísmo helenístico, por vezes em oposição ao judaísmo palestino. Neste artigo, reflito sobre o conceito de judaísmo helenístico a partir de referências a casos pontuais de textos e autores comumente alocados em tal âmbito. Demonstro a frequente simplificação que a expressão estabelece para um fenômeno intercultural extremamente completo. Não sugiro a abolição do uso da mesma, mas sim seu uso refletido e com o reconhecimento da necessidade de se considerar as diversidades existentes.